Neutrophils Play an Important Role in Host Resistance to Respiratory Infection with Acinetobacter baumannii in Mice - van Faassen, Henk (American Society for Microbiology (ASM), 2007)
Acinetobacter baumannii has emerged as a major cause of both community-associated and nosocomial pneumonia, but little is known about the cellular and molecular mechanisms of host defense against respiratory infection with this bacterial pathogen. In this study, we examined the role of neutrophils in host resistance to pulmonary A. baumannii infection in a mouse model of intranasal (i.n.) infection. We found that neutrophils were rapidly recruited to the lungs following i.n. inoculation of the pathogen and declined to baseline level upon clearance of the infection. Depletion of neutrophils using monoclonal antibody RB6-8C5 prior to infection resulted in an acute lethal infection that was associated with enhanced bacterial burdens in the lung (P < 0.05) and extrapulmonary dissemination to the spleen. The increased susceptibility to A. baumannii in neutropenic mice was associated with a delay in the mRNA expression and production of early proinflammatory cytokines such as tumor necrosis factor alpha, interleukin-6, keratinocyte chemoattractant protein, monocyte chemoattractant protein 1, and macrophage inflammatory protein 2 (MIP-2) in the lungs and development of severe bronchopneumonia and lymphoid tissue destruction in the spleen. Moreover, i.n. administration of the neutrophil-inducing chemokine MIP-2 to normal mice induced a pulmonary influx of neutrophils and significantly enhanced the clearance of A. baumannii from the lungs (P < 0.01). These results imply that neutrophils play a critical role in host resistance to respiratory A. baumannii infection.